Gains in bank mergers: Evidence from the bond markets - Penas, Marı́a Fabiana; Unal, Haluk (Journal of Financial Economics, 2004)
We present evidence that the adjusted returns of merging banks’ bonds are positive and significant across pre-merger and announcement months. The cross-sectional evidence indicates that the primary determinants of merger-related bondholder gains are diversification gains, gains associated with achieving too-big-to-fail status, and, to a lesser degree, synergy gains. We obtain the same finding when we examine the acquiring banks’ credit spreads on new debt issues both before and after the merger. We also provide the first study that shows acquirers benefit by the lower cost of funds on post-merger debt issues.